Promoting the Pancasila Students’ Profiles through Mathematics Education in Schools: Ethnomathematics Roles - Hendriyanto, Agus; Juandi, Dadang; Kuncoro, Krida Singgih; Fitriana, Laila; Sahara, Sani; Muhaimin, Lukman Hakim (FKIP Universitas Lampung, 2023)
The Function of Ethnomathematics in the Development of Pancasila Student Profiles for Indonesian Students Via Mathematics Education in Schools. The present mathematics curriculum in Indonesia (IND) places a strong emphasis on the creation of a Pancasila student profile in order to ensure that pupils are learning mathematics in a meaningful way. This paper suggests an integration of ethnomathematics into the formal mathematics curriculum as one approach to dealing with these learning issues. It is based on a literature assessment of studies on ethnomathematics, mathematics education, and Pancasila student profile. The literature review method used with a narrative review design. A total of 28 articles were selected for publication at the final stage of the review process. In light of the preceding explanation, it is clear that ethnomathematics plays a part in the formal school mathematics curriculum since the context-relevant and constraint-filled problem-solving techniques give many abstract mathematical notions the required contextual meaning. Keywords: ethnomathematics, mathematics education, pancasila student profiles.DOI: http://dx.doi.org/10.23960/jpp.v13.i2.202305